Planificación estratégica y gestión del turismo en la gerencia regional de comercio exterior y turismo de Loreto 2024 - Uriarte Sanchez, Sharon Sarita (2025)
This research was conducted with the aim of analyzing the relationship between strategic planning and tourism management. A descriptive correlational approach and a non-experimental design were used. The sample consisted of 25 employees, who were given a questionnaire to gather the necessary information. The results indicated a significant relationship between strategic planning and tourism management, evidenced by a correlation coefficient of Rho 0.716 and a significance of 0.000. Regarding specific dimensions, strategy formulation showed a correlation coefficient of (r=0.725; p=0.000), local planning had (r=0.612; p=0.000), and strategy evaluation presented (r=0.681; p=0.000), all indicating a significant relationship with tourism management in GERCETUR 2024.